Marketing Strategy for Griya's Micro-small Medium Enterprises' Product in Tanjung Jaya Village - Goenadhi, Felix; Utami, Ajeng Sekar; Usman, Meiske Aulia; Prayoga, Tasya Zahwa; Rahmiati, Filda (AIBPM Publisher, 2023)
Marketing mix is a tool to increase enterprise sales and engage consumer to purchase the products. The purpose of this study is to analyze the internal assessment and the relevant marketing mix strategy's application to boost sales at Griya in Tanjung Jaya Village. This study employs a qualitative descriptive analytic approach, gathering information from the firm directly through observations and interviews tailored to the research topic. The results of this study indicates that the strategy applied by Griya products in Tanjung Jaya Village has been going well, where the four marketing strategy elements play distinct marketing roles while supporting and complementing one another. It is better if the Griya MSME in Tanjung Jaya Village are improved with the marketing mix that has been implemented. Given that many of the company's rivals are releasing goods that are comparable to its own, the company's approach is solid and many contributing marketing aspects should be re-examined in order to increase the number of consumer as well as maintain sales and increase their consumer intention to purchase the services.